Memória Art Déco em Goiânia: a busca por uma identidade - Angelica Fernandes Azevedo (2018)
Goiânia, the new capital of the State of Goiás, is conceive according to the principles of modernity during the 30s. The symbols of modernity are vested through a rational urban planning, among hygienists ideals with aspirations that could come across a new modern capital for the state. The Art Déco architecture style brings the modernity from that era whose were distinct from the ancient colonial capital, the city of Goiás. Passed by more than eighty years since the foundation, Goiânia showed substantial modifications in his urban scenario, because among with his speed economic and territorial expansion, the modern ideal inspired by the pioneers of the construction of the new capital, where modified, reflecting directly in the personals relations between the Setor Central and the residents of the capital. Therefore, the research intends to assay if the Art Déco, style constituted in Goiânia by the implantation of a pioneer set of buildings and monuments in the Setor Central, can establish a significant identity of the goianienses. Also, the study intends to: understand how the facades occulted by announcements affects the (des) construction of his identity; set up the actual actions of valorization of the Art Déco in Goiânia; identify the identity relation between the residents and the Déco style. As a method of research, theres the tabulation about memory, nostalgia and identity, followed by the social investigation with a representative number of residents in Goiânia. In another moment, there whore heard from the specialists involved with the actions of valorization of the Déco buildings, about the questions of identity. It is assumed that, the construction of identity is involved with the distinct age range of the population, which attributes significations and affections according to the memories and experiences transformed by the time and space.